OPTIMIZATION DOSE BNCT OF SKIN CANCER WITH SHIELD-HIT 12A PROGRAM - Sri Mulya winingsih (Fakultas Sains dan Matematika Universitas Kristen Satya Wacana, 2019)
Study aims to determine the optimum dose of cancer therapy Boron Neutron Cancer Therapy (BNCT) in skin cancer using SHIELD-HIT 12A program. The steps taken are to define the geometry and components of the skin as the object being studied and boron-10 as the source of radiation used. The output obtained from SHIELD-HIT 12A is in the form of radiation length in each skin forming constituent of skin. Medium 1 is a bone tissue with a radiation length of 10.416 cm; medium 2 is muscle tissue with radiation length 20.089 cm; medium 3 is skin tissue with radiation length 34.25 cm and medium 4 is cancer tissue with radiation length 9.639 cm. In this study the dose of BNCT has not been detected by the SHIELD-HIT 12A program.